The level of awareness among Muslims employees of Felda Palm Industries Sdn Bhd towards Islamic pre-need funeral plan in Kuala Lumpur / Mohamad Sha’hrul Rizal Mohd Khalil - Mohd Khalil, Mohamad Sha’hrul Rizal (Faculty of Business Management, 2017)
Purpose – The purpose of this study is to investigate the awareness level among Muslims regarding Islamic pre-need funeral service and identify antecedents affecting level of awareness for Islamic pre-need funeral service. Specifically, there are four research objectives: To study awareness level (RO1), to determine any significant difference between gender (RO2), to investigate association between social influence, perception and religiosity with awareness level (RO3) and to identify most influential factor for awareness of Islamic pre-need funeral plan (RO4) Methodology – 105 respondents for Felda Palm Industries Sdn Bhd were selected using stratified random-sampling technique. Questionnaire consists of 2 sections which are demographic and questions on variables: social influence, perception and religiosity and awareness. Descriptive statistics, t-test, correlation and regression are used to answer research objectives. Finding – It is found that awareness level among employees is moderate (RO1). It also found that there is no significant difference between male and female in term of awareness (RO2). Social influence and perception have significant relationship with awareness of Islamic pre-need funeral service (RO3). The results also show that social influence is the most influential factor toward Islamic pre-need funeral service (RO4). Practical Implication – Service provider should realize that media referent and word of mouth play a major role in influencing consumer as social influence for this study has the most impact toward awareness of Islamic pre-need funeral plan. Therefore, they should enhance more advertising and personal selling to create Muslims awareness on Islamic pre-need funeral plan. Keywords – Muslims, Islamic pre-need funeral plan, awareness, social influence, perception, religiosity. Paper Type – Research paper.